Uterine conservative–resective surgery for selected placenta accreta spectrum cases: Surgical–vascular control methods - Rozi Aditya Aryananda; Aditiawarman Aditiawarman; Khanisyah Erza Gumilar; Manggala Pasca Wardhana; M. Ilham Aldika Akbar; Nareswari Cininta; Ernawati Ernawati; Budi Wicaksono; Hermanto Tri Joewono; Erry Gumilar Dachlan; Citra Aulia Bachtiar; Devita Kurniawati; et al. (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction The incidence of placenta accreta spectrum (PAS) has increased, but the optimal management and the optimal way to achieve vascular control are still controversial. This study aims to compare maternal outcomes between different methods of vascular control in surgical PAS management. Material and methods A retrospective cohort study on consecutive cases diagnosed with PAS between 2013 and 2020 in single tertiary hospital. The final diagnosis of PAS was made following preoperative ultrasound and confirmation during surgery. Management of PAS using cesarean hysterectomy with internal iliac artery ligation (IIAL) was compared with two types of vascular control in uterine conservative–resective surgery (IIAL vs identification–ligation of the upper vesical, upper vaginal, and uterine arteries). Results Over an 8‐year period, 234 pregnant women were diagnosed with PAS meeting the inclusion criteria. Uterine conservative–resective surgery (200 cases) was associated with lower mean blood loss compared with cesarean hysterectomy with IIAL (34 cases) in all PAS cases (1379 ± 769 mL vs 3168 ± 1916 mL; p < 0.001). In sub‐analysis of the two uterine conservative–resective surgery subgroups, the group with identification–ligation of the upper vesical, upper vaginal, and uterine arteries had a significantly lower blood loss compared with uterine conservative–resective surgery with IIAL (1307 ± 743 mL vs 1701 ± 813 mL; p = 0.005). Women in the hysterectomy with IIAL group had more massive transfusion (35.3% vs 2.5%; p < 0.001; odds ratio [OR] 21.3, 95% confidence interval [CI] 6.9–66), major blood loss (>1500 mL) (70.6% vs 34%, p < 0.001; OR 4.7; 95% CI 2.1–10.3), catastrophic blood loss (>2500 mL) (64.7% vs 12.5%;p < 0.001; OR 12.8, 95% CI 5.7–29.1), other complications (32% vs 12.4%; p = 0.007; OR 3.4, 95% CI 1.5–7.7), and intensive care unit admission (32.4% vs 1.5%; p < 0.001; OR 31.4, 95% CI 8.2–120.7) compared with the uterine conservative–resective surgery groups. The identification–ligation of the upper vesical, upper vaginal and uterine arteries had a significant lower risk for major blood loss (30.5% vs 50%; p = 0.041; OR 0.44, 95% CI = 0.2–0.9) compared with IIAL for vascular control of uterine conservative–resective surgery. Conclusions Cesarean hysterectomy is not the default treatment for PAS, PAS with invasion above the vesical trigone are suitable for uterine conservative–resective surgery with upper vesical, upper vaginal and uterine artery vascular control.